Midnight Report: A Novel Faculty-Guided Night Curriculum to Enhance Resident Nighttime Education. Issue 5 (May 2020) - Al-Khafaji, Jawad; Konjeti, Venkata Rajesh; Call, Stephanie
Abstract : Objectives: A large discrepancy exists in resident educational activities between daytime and nighttime medical rotations. The Accreditation Council for Graduate Medical Education duty-hour regulations led to the increased adoption of the dedicated nighttime rotation called night float. Nighttime education has largely been negatively perceived by night float medical residents. Although there have been attempts to improve nighttime education, none of the initiatives included faculty-guided structured night curriculum. Our objective was to improve resident experience with and perception of nighttime education by implementing a structured, faculty-guided, nighttime educational curriculum. Methods: This was an assessment of an educational initiative at a single academic medical center, Virginia Commonwealth University Health System. The internal medicine residency program implemented a teaching nocturnist program in 2013 and a novel faculty-guided nighttime teaching curriculum in 2016 called midnight report. We then evaluated resident experience with and perception of nighttime education at our institution using anonymous free-response surveys for the academic year July 2016–June 2017. Results: Of the 142 eligible residents, 95 (67%) responded to the survey. The majority of the residents (54%–77%) positively perceived their experience of the nighttime educational environment during their night float rotation after implementation of the teaching nocturnist program and midnight report. Conclusions: Compared with the published literature reporting negative perceptions of the nighttime educational environment by residents at different academic centers, our results showed that the majority of our residents positively perceived the impact of our new faculty-guided nighttime educational curriculum. Abstract : Nighttime medical education, or the lack thereof, historically has been perceived negatively by residents. This article explores a unique opportunity to enhance nighttime resident education by creating a novel night curriculum with the support of teaching nocturnists and studying resident perceptions and satisfaction with nighttime education after implementing the new curriculum.